2019
DOI: 10.1017/s1743923x19000515
|View full text |Cite
|
Sign up to set email alerts
|

International Organizations, Nongovernmental Organizations, and Police Implementation of Domestic Violence Policies in Liberia and Nicaragua

Abstract: Domestic violence is the predominant form of violence against women in most countries in Africa and Latin America. Scholars have theorized the adoption of domestic violence laws and policies in both regions. However, policy implementation is understudied and under theorized. Therefore, we compare how international organizations and women's nongovernmental organizations have influenced the implementation of domestic violence policies by police officers in Liberia and Nicaragua. We introduce the concept of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In 2016, during the fieldwork for this study, the Comisarias de la Mujer y la Niñez were closed down by the government without explanation. 34 In April, 2018, shortly before the findings of this study were to be presented in Nicaragua, the national police opened fire with live ammunition on students protesting social security reforms. To date, over 325 individuals have been killed, and over 2000 wounded, most of them unarmed protesters.…”
Section: Bmj Global Healthmentioning
confidence: 97%
“…In 2016, during the fieldwork for this study, the Comisarias de la Mujer y la Niñez were closed down by the government without explanation. 34 In April, 2018, shortly before the findings of this study were to be presented in Nicaragua, the national police opened fire with live ammunition on students protesting social security reforms. To date, over 325 individuals have been killed, and over 2000 wounded, most of them unarmed protesters.…”
Section: Bmj Global Healthmentioning
confidence: 97%
“…Their efforts have been successful (Htun and Weldon, 2012;Weldon, 2002a;Weldon et al, 2011;Medie and Walsh, 2019). Particularly since the 1979 United Nations' (UN) Convention for the Elimination of All Forms of Discrimination Against Women (CEDAW) 2 , the Vienna Declaration from 1993, and the Beijing Declaration and Platform for Action from 1995, there has been a global effort to better understand the dynamics of gender-based violence and to identify targeted policy instruments to eradicate it (Macaulay, 2000).…”
Section: The Case Of Brazilmentioning
confidence: 99%
“…In addition, social movements tend to be more active in more urban and highly populated areas (Uitermark et al, 2012). Previous work has shown that women's movements are crucial for policy adoption (Htun and Weldon, 2012;Weldon, 2002a;Weldon et al, 2011;Medie and Walsh, 2019), so it is also possible that policy demand varies depending on urbanization and population size. Accordingly, we employ data from the 2010 IBGE census to add controls for the share of women in the population (% women population), the share of the population who live in urban areas (% urban population), and population size (log) 8 .…”
Section: Study 1: Municipal-level Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, countries have passed laws to criminalize acts such as intimate partner violence, rape, and early marriage. Some countries have also established specialized criminal justice sector mechanisms to address gender-based violence (Medie 2020;Medie and Walsh 2019). These include specialized police units, prosecutorial units, and courts, to respond to various forms of gender-based violence.…”
Section: Introductionmentioning
confidence: 99%